Geração de corrente spin polarizada em heteroestruturas dopadas com impurezas magnéticas - Pereira, Pedro Henrique (Universidade Federal de São Carlos, 2015)
In this dissertation, the computational modeling of two semiconductor structures composed of two quantum wells was performed, being a quantum well doped with magnetic impurities. Each structure was designed to form a three-level electronic sys- tem, whose energy values favor scattering Lambda when photons affect the structure. This type of scattering consists of the transition of the electron, initially confined at a low energy level, to a higher energy level, with subsequent capture to a lower third energy level than the second. The three levels lie in different confining layers that follow each other along the length of the structure, before an extended region of exit, in which the electron is free to contribute to the photocurrent. The terminology refers to the ”path”made by the electron in a diagram of energy versus position. The elec- tron rises to the highest intermediate level, and instead of being ejected in the second transition, it is recaptured before it can contribute to photocurrent generation. The effect is resonant, to achieve it, two lasers, one of each fixed frequency and another variable are included in the model. The magnetic doping in the second quantum quantum makes its potential dependent on the spin of the electron. Thus, the trap- ping frequency is spin-dependent ie the trapping of the spin component is selective at the frequency of the trapping field. To perform the calculations, the time-dependent Schrdinger equation for the conduction band was solved numerically within the effec- tive mass approximation using the split-operator method. The resonant frequencies were obtained by calculating of the absorption spectrum and also the condition of not allowing the optical transition between each fundamental state of each well was veri- fied. The spectral response of the photocurrent was studied in the resonant regime. It was verified the appearance of an attenuation of the amplitude of the photocurrent with the increase of the intensity of the trapping field, evidencing the phenomenon of the coherent trapping population. The projection of the wave function evolved over time in each eigenstate of the three-level system showed the formation of the dark state. This state is a linear combination of each ground state and its main feature is to block the transition to the higher energy state, leaving the system inert to the electromagnetic field. This proposed heterostructure showed a high degree of spin se- lectivity, thus being a strong candidate for a spin polarized photocurrent generating device.
Generation of polarized spin current in heterostructures doped with magnetic impurities
Keywords: Geração de corrente polarizada em spin; Semiconductor magnético diluído; Aprisionamento coerente de população; Método Split-Operator; Dispositivos semicondutores; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA DA MATERIA CONDENSADA::ESTADOS ELETRONICOS